Tangible and intangible cultural drivers of international students’ retention in China - Jiyagatai; Chenfang, Shi (Frontiers in Education, 2025)
Although China has become an increasingly attractive destination for international education, the determinants of international students’ post-graduation retention remain underexplored. This study analyzed survey data from 643 international students to assess how perceptions of Chinese culture influence intentions to work, invest, or immigrate after graduation. Using exploratory factor analysis (EFA), three cultural dimensions—Tangible Culture, Intangible Culture, and Cultural Education—were identified. Confirmatory factor analysis (CFA) verified the factor structure, demonstrating high internal consistency (Cronbach’s α = 0.90) and strong construct validity. Structural equation modeling (SEM) revealed that Tangible Culture was the strongest predictor of intentions to work (β = 0.23, p < 0.001) and invest (β = 0.24, p < 0.001) in China, followed by Intangible Culture and Cultural Education, which also exerted significant positive effects. Stay intention was shaped directly by these cultural dimensions and indirectly through work and investment intentions. The findings suggest that integrating cultural immersion with education–employment pathways can strengthen China’s capacity to attract and retain international talent.